Ecologia alimentar de Iphisa e. elegans (Gray, 1851) (Squamata: Gymnophthalmidae) na flona do Tapajós e nos municípios de Beruri e Maraã no Amazonas, Brasil - CONCEIÇÃO, Luan Martins (2022)
South America has the most diverse herpetofauna in the world, only in Brazil there are more than 282 species of lizards, 154 of which are endemic. Lizards are present in the most diverse types of habitats and their presence in these environments is influenced by biotic and abiotic factors. Dietary studies serve as a basis for understanding the life history of species, and serve as a theoretical basis for areas such as trophic ecology, trophic niche and interactions with other organisms in their habitats. In this work, some aspects of the trophic ecology of I. e. elegans, a small lizard that inhabits the leaf litter of the Amazon rainforest. Thus, the following questions were raised: i) What types of prey are used by I. e. elegans?; ii) Which types of prey are most important for food for the species?; iii) I. e. elegans is a specialist diet lizard or a generalist? The specimens studied come from three locations in the Amazon Region: Amanã/Amazonas, Beruri/Amazonas and Santarém/Pará. To assess the contribution of food items, the frequency of occurrence (FOi%), the Volume of each item (V%), the Food Importance Volumetric Index (IVAi) and the Trophic Amplitude Index were measured. 37 specimens were examined (26 from Tapajós, 5 from Maraã and 6 from Beruri). A total of 5 food items (Blattaria, Araneae, Orthoptera, Scorpiones and Vegetables) were recorded. It was observed that the FOi% of prey categories was as follows: Blattaria (55.56%), Araneae (37.04%), Orthoptera (22.22%), Scorpiones (3.70%) and material vegetable (7.41%). The IVA% presented the following values: Blattaria (73.96%), Araneae (16.84%), Orthoptera (8.54%), Scorpiones (0.17%) and Vegetables (0.48%). The Levins Trophic Amplitude resulted in: Ba = 0.360. The results indicate that I. e. elegans have a diet with a high proportion of cockroaches, spiders and orthoptera, respectively. The consumption of arthropods has a high nutritional and energy value for the diet of these lizards. This assessment provided us with important information about this species, such as the specialist characteristic of its food ecology. These results will contribute to further studies on I. e. elegans and their ecological diversity, promoting a greater understanding of ecological patterns within Gymnophthalmidae.